Dual-task interventions reduce vividness and unpleasantness in both old and new memories - van Schie, Kevin (Behaviour research and therapy, 2025)
A core element of EMDR therapy is that a patient recalls a traumatic memory while concurrently making horizontal eye movements. Experimental studies show that performing such tasks simultaneously (i.e., Recall + Dual-Task) reduces the memory's vividness and unpleasantness. Memory age may act as a boundary condition on this effect as older memories have been more consolidated and strengthened over time compared to more recently formed memories, making older memories less susceptible to change. To investigate this, participants (N = 195) in Experiment 1 recalled an old or a new negative autobiographical memory and were randomly assigned to a Recall + Dual-Task intervention or a Recall Only intervention. Before, during, and after the intervention the memory was rated on vividness and unpleasantness. In Experiment 2 (N = 356) a follow-up rating was added one day later to test for delayed effects of memory age on intervention effectiveness. Collectively, the two experiments show that Recall + Dual-Task immediately reduces memory vividness and unpleasantness compared to Recall Only. For unpleasantness this differential effect remained one day later. However, none of the effects were moderated by memory age. Thus, these findings suggest that memory age is not a boundary condition for dual-task effectiveness and that dual-task interventions (as used in EMDR) could be similarly effective for reducing the intensity of emotional memories of different ages. •Recall + Dual-Task interventions reduce memory vividness and unpleasantness.•Dual-task interventions showed lasting effects on memory unpleasantness.•Memory age did not moderate the effects of dual-task interventions.•Results suggest dual-task interventions can be effective for all memory ages.